Quick Response Code Indonesian Standard (QRIS) Educational Activities Through Socialization to Increase Knowledge and Interest in Use by the Community in Dauh Puri Kaja Village - Ida Nyoman Basmantra; Nathasia Liman (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Technology is changing very fast at this time. All things are affected, one of them which is the economy. There are many digital payment instruments that can be found and used in Indonesia. The Quick Response Code Indonesian Standard (QRIS) is a standard issued by Bank Indonesia to make transactions more efficient, financial inclusion in Indonesia faster, promote UMKM, and ultimately encourage economic growth. After collecting data through surveys, the authors designed socialization activities regarding QRIS so that the public would have a more in-depth understanding of how it is used for daily transactions. The results of this socialization activity will help the local community to make transactions easier and participate in improving the Indonesian economy in the future.